(untitled) - Zhao, Yong; Yong Zhao (San Francisco, CA, 2014)
Who's Afraid of the Big Bad Dragon? by award-winning writer Yong Zhao offers an entertaining, provocative insider's account of the Chinese school system, revealing the secrets that make it both "the best and worst" in the world. Born and raised in China's Sichuan province and a teacher in China for many years, Zhao has a unique perspective on Chinese culture and education. He explains in vivid detail how China turns out the world's highest-achieving students in reading, math, and science—yet by all accounts Chinese educators, parents, and political leaders hate the system and long to send their kids to western schools. Filled with fascinating stories and compelling data, Who's Afraid of the Big Bad Dragon? offers a nuanced and sobering tour of education in China
Includes bibliographical references (pages 217-223) and index
Keywords: Education and state; Educational anthropology; Educational sociology; Academic achievement